2015
DOI: 10.1016/j.jval.2015.09.1887
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Formal Risk Sharing Agreements (Rsa): A Promising Solution for Sustainable and Predictable Pharmaceutical Expenditures In Bulgaria

Abstract: A571by the health insurer. The IT systems of health insurers and hospitals need to be adapted. RecommendAtions: A working group led by the pharma industry association and major health insurers (including pharma companies, hospital administration and oncologists) will set up pilots with oncology clinics to test the feasibility of implementing an indication code and work on sustainable pricing models for TCRs. conclusion: Goal would be a standardised processing of the remuneration for TCRs based on indication co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…In Hungary, an analysis on the cost of treatment with new antiviral therapies for hepatitis C virus (HCV) by Kocsis et al [ 61 ] was submitted to the HTA agency, which found that the introduction of these new drugs placed a financial strain on payers. As such, RSAs appear to be a promising solution for balancing payer uncertainty with the market access for new medicines in Eastern Europe [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Hungary, an analysis on the cost of treatment with new antiviral therapies for hepatitis C virus (HCV) by Kocsis et al [ 61 ] was submitted to the HTA agency, which found that the introduction of these new drugs placed a financial strain on payers. As such, RSAs appear to be a promising solution for balancing payer uncertainty with the market access for new medicines in Eastern Europe [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Contractual specifications vary according to setting and so do the implementation conditions; for example, Belgium requires inclusion of price, compensatory measures for budgetary risk, reporting modalities, and other legal requirements in each MEA contract, while France, Lithuania, and Portugal require the regular submission of sales data by the manufacturer; to obtain permanent reimbursement after conditional reimbursement through MEA comes to an end, manufacturers need to provide Czech, Dutch, Portuguese (only for some CED schemes) and Swedish authorities the evidence (usually on cost‐effectiveness or use) initially requested by the agency (Ferrario and Kanavos, ). MEAs – predominantly financial agreements – are also implemented in Estonia, Hungary and Poland (Ferrario et al., ; Kwong et al., ; Zawodnik et al., ), while Bulgaria has taken concrete steps to prepare the ground for their implementation (Petrov and Hubenov, ) while Romania and Greece are also concluding their first MEAs in, 2016 in the area of hepatitis C.…”
Section: Introductionmentioning
confidence: 99%
“…Existe enfasis en procurar un diseño simple capaz de resolver eficientemente incertidumbres y gestionar riesgos, y ajustado a la realidad local. 13,17,21,22 Las lecciones se concentran en la identificaci on de la enfermedad y tratamientos cuyas caracterı ´sticas faciliten la aplicabilidad de un ARC. Las referencias recomiendan idealmente tecnologı ´as nuevas orientadas a enfermedades prioritarias con pocos o sin tratamientos efectivos, o con necesidades insatisfechas.…”
Section: Lecciones Para El Diseño E Implementaci Onunclassified
“…1e3,17 Tabla 1 -Modelo propuesto de ARC: Comparaci on entre modelos actuales y modelo propuesto con base en la experiencia internacional. 1,3,8,11,14,17,31 Actor Caracterı ´sticas y rol…”
Section: Lecciones Para El Diseño E Implementaci Onunclassified
See 1 more Smart Citation